2010
DOI: 10.1176/appi.ajp.2010.09050692
|View full text |Cite
|
Sign up to set email alerts
|

Performance-Based Measures of Everyday Function in Mild Cognitive Impairment

Abstract: Objective-The view that everyday function is preserved in mild cognitive impairment may be problematic. The objectives of this study were to determine the magnitude of impairment in everyday function in patients with mild cognitive impairment and Alzheimer's disease using a novel sensitive performance-based measure (the UCSD Performance-Based Skills Assessment; UPSA), contrast it with use of an informant-based measure (the Alzheimer's Disease Cooperative Study-Activities of Daily Living Inventory; ADCS-ADL), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
110
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(126 citation statements)
references
References 43 publications
6
110
0
8
Order By: Relevance
“…In a preliminary study we compared patients with MCI, patients with mild AD who by diagnosis have functional impairments, and healthy age matched controls on the UPSA, as well as measures of cognition (e.g., episodic memory, semantic memory, executive function, speed). We found that patients with MCI had compromises in everyday functional competence and that the UPSA was strikingly sensitive to these (Goldberg et al, 2010). Additionally the UPSA outperformed an informant based measure on a variety of criteria.…”
Section: Introductionmentioning
confidence: 78%
“…In a preliminary study we compared patients with MCI, patients with mild AD who by diagnosis have functional impairments, and healthy age matched controls on the UPSA, as well as measures of cognition (e.g., episodic memory, semantic memory, executive function, speed). We found that patients with MCI had compromises in everyday functional competence and that the UPSA was strikingly sensitive to these (Goldberg et al, 2010). Additionally the UPSA outperformed an informant based measure on a variety of criteria.…”
Section: Introductionmentioning
confidence: 78%
“…Those scales include the CDR [4,5], the FAQ [4,5], the ADL-Prevention Instrument (ADL-PI) [24], and the Everyday Cognition [25]. Two performance-based IADL instruments have also been shown to successfully distinguish between CN elderly and MCI: the University of California, San Diego Performance-Based Skills Assessment [26] and the Financial Capacity Instrument [27]. All of these tests are clearly sensitive to early changes in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated that patients with MCI show significantly compromised functional abilities when evaluated with performance-based measures, and this trend extends to patients identified as having intact functioning by family members (Goldberg et al, 2010).…”
Section: Hypothesis #5: Can Daily Functioning Be Used To Predict Convmentioning
confidence: 99%
“…However, the results of this study do not support this delineation as both converters and nonconverters presented with functional decrements. In addition, prior research also points to this delineation as problematic for a number of reasons (Goldberg et al, 2010). First, medical and psychiatric conditions that are reliably associated with cognitive changes are, in turn, also reliably associated with changes in everyday functioning (Goldberg et al, 1990;Heaton et al, 1994).…”
Section: Hypothesis #5: Can Daily Functioning Be Used To Predict Convmentioning
confidence: 99%
See 1 more Smart Citation